Menggali Kreativitas Seni pada Anak Berkebutuhan Khusus - Muhammad Imam Tobroni (Humaniora, 2013)
Some people see children who have behaviors and habits are unusual or out of the general habit. They are ostracized, even sometimes are considered strange, cannot socialize, have lives and have fun for theirselves, even worse they are considered abnormal. People sometimes see from the surface, passing judgment of the physical without investigating the cause of why it happened. Child with special needs, or autism, is one of them. Despite of its uniqueness, it turns out that children who have special needs have extraordinary ability, especially in terms of artistic creativity. Unique paintings and the ability to express feeling should be enhanced to take advantage of the ability of the child maximally, of course with the consistent help to find the child’s ability actually.